Does More Public Health Spending Buy Better Health? - James Marton; Jaesang Sung; Peggy Honore (SAGE Publishing, 2015)
Background: In this article, we attempt to address a persistent question in the health policy literature: Does more public health spending buy better health? This is a difficult question to answer due to unobserved differences in public health across regions as well as the potential for an endogenous relationship between public health spending and public health outcomes. Methods: We take advantage of the unique way in which public health is funded in Georgia to avoid this endogeneity problem, using a twelve year panel dataset of Georgia county public health expenditures and outcomes in order to address the "unobservables" problem. Results: We find that increases in public health spending lead to increases in mortality by several different causes, including early deaths and heart disease deaths. We also find that increases in such spending leads to increases in morbidity from heart disease. Conclusions: Our results suggest that more public health funding may not always lead to improvements in health outcomes at the county level.